ANALISIS PROSES PACKAGING DAN STUFFING PERUSAHAAN FURNITUR LOKAL DALAM MENJAGA EKSISTENSI PERSAINGAN GLOBAL (STUDI KASUS: UD SURYA ABADI FURNITURE, SUKOHARJO, JAWA TENGAH) - Yogi Pasca Pratama; Dicky Afisena; Bambang Sarosa (Jurnal Manajemen Industri dan Logistik (JMIL), 2018)
Indonesia has great potential in developing the furniture industry sector. The abundance of raw materials and high labor numbers should be optimized to encourage the furniture industry in Indonesia in the international furniture trade. However, in reality, the Indonesian furniture industry has increasingly been eliminated in the arena of international furniture trade. Therefore, it is necessary to consider how the furniture industry actually manages the company. One of the influential factors in furniture exports is how to manage the supply chain or logistics of the furniture industry, where one of them is related to the process of packaging and stuffing of furniture products. As a representation, this study tries to describe how the packaging and stuffing process is carried out by UD Surya Abadi Furniture, one of the furniture industries located in Sukoharjo Regency, Central Java. This research is a descriptive study, where data is collected by observation, interview, and documentation techniques. The results of this study discuss the packaging procedures, materials used and feasibility tests, and how the procedures and benefits obtained from the stuffing process at UD Surya Abadi Furniture. The conclusion obtained is that the description of the packaging and stuffing process that is carried out is quite good with the use of materials that meet the standards. Nevertheless, the process of packaging and stuffing at UD Surya Abadi Furniture is still done with manual counting so that it is not optimal.